Effect of growing media, pinching and paclobutrazol on growth and flowering of Barleria cristata for suitability as pot plant - THAKUR, PRIYANKA; NICHAL, VIKRAM; DHIMAN, S R; GUPTA, Y C (The Indian Journal of Agricultural Sciences, 2015)
A study was conducted to see the effect of three growing media (soil from natural habitat, soil from natural habitat and FYM (2:1), v/v and soil, sand and FYM (2:1:1), three pinching treatments (No pinch, single pinch and double pinch) and paclobutrazol (0, 75, 150 ppm) on growth and flowering of seedlings as well as vegetatively propagated (rooted stem cuttings) of Phillipines violet or blue bell barleria (Barleria cristata L.). Plants raised through seeds and rooted cuttings differed significantly among themselves for various growth and flowering parameters. Plants raised under both methods of propagation showed optimum plant height (1.5 to 2.5 times to the height of the pot) when grown in soil from natural habitat and FYM with single and double pinching in absence of application of paclobutrazol for growing as pot plant. Seedlings recorded maximum number of secondary side shoots (20.58), leaves (177.42), flower clusters (16.17), flowers (23.58)/plant when grown in soil from natural habitat and FYM with double pinching and with the application of 75 ppm paclobutrazol and seed raised plants showed early visible bud formation and flowering when grown in all growing media without pinching and application of 75 ppm paclobutrazol. However, the cutting raised plants recorded maximum number, of secondary side shoots (16.00), leaves (171.67), flower clusters (17.83), flowers (24.42)/plant when grown in soil from natural habitat and FYM with double pinching and with the application of 75 ppm paclobutrazol. Seed raised plants showed better results in case of plant height, length of primary side shoots and plant spread than cutting raised plants while cutting raised plants recorded early visible bud formation and flowering and maximum number of flower clusters/plant than seed raised plants. Based on the findings of present investigations, seed raised Barleria cristata. plants grown in pots containing soil from natural habitat added with FYM (2:1, v/v), double pinching and application of 75 ppm paclobutrazol is recommended for better growth and flowering.